2020
DOI: 10.1186/s12877-020-01757-8
|View full text |Cite
|
Sign up to set email alerts
|

Frailty phenotype and multi-domain impairments in older patients with chronic kidney disease

Abstract: Background Older subjects with chronic kidney disease (CKD) are often affected by multiple geriatric impairments that may benefit from a comprehensive geriatric assessment (CGA). However, ordinary execution of CGA in all these individuals would be unaffordable. We evaluated if Frailty Phenotype (FP) could identify older CKD-patients that may benefit the most from a CGA. Methods We evaluated 112 CKD patients not yet on dialysis (age ≥ 65 years, eGFR < 45 ml/min). FP was defined according to the criteria pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 30 publications
0
22
0
4
Order By: Relevance
“…Several reasons may be responsible for the observed relationship between frailty and the UTI risk. Patients with frailty frequently have co-existing malnutrition and other geriatric syndromes including sarcopenia, cognitive dysfunction, and/or depression [ 40 , 41 ]. Prior studies showed that having low mini-nutrition assessment (MNA) scores was associated with an increased UTI risk [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several reasons may be responsible for the observed relationship between frailty and the UTI risk. Patients with frailty frequently have co-existing malnutrition and other geriatric syndromes including sarcopenia, cognitive dysfunction, and/or depression [ 40 , 41 ]. Prior studies showed that having low mini-nutrition assessment (MNA) scores was associated with an increased UTI risk [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we documented how progressively impaired renal function also entailed impaired performance status, with patients requiring more intensive care. Accordingly, the impaired renal function seems to be a clinical feature, able to significantly impact on older patients in terms of frailty [2,3,16] and intrinsic capacity [17]. Furthermore, while the impact of impaired renal function on outcomes has been already described [20,21], with previous studies showing how CKD (eCrCl < 60 mL/min) is associated with short-term outcomes [18,19], the peculiarities of our analysis help us to document and underline this relationship also in a "real-life" older cohort observed over a significant follow-up time.…”
Section: Discussionmentioning
confidence: 99%
“…The result of these abnormalities, independent of the cause, leads to decreased glomerular filtration rate (GFR) with onset of chronic kidney disease (CKD) [1]. In older individuals, CKD is recognized as one of the main comorbidities, associated with an impaired clinical and functional status [2,3], increased hospitalization, and a higher risk of major clinical outcomes [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pessoas idosas frágeis são quatro vezes mais propensas a terem depressão do que as não frágeis ou robustas179 . Na população com DRC, um estudo que avaliou idosos em tratamento conservador observou uma prevalência de 45% de fragilidade e 50% de depressão nos pacientes frágeis180 . Depressão e fragilidade apresentam-se na literatura como entidades bidirecionais, mas não estão claras as relações de causalidade, em que medida são fenômenos sobrepostos ou, ainda, síndromes distintas177,179 .…”
unclassified